The M.A.STE.R.S algorithm for acute visual loss management after facial filler injection - Graue, Gerardo; Ochoa Araujo, Dora Aline; Plata Palazuelos, Cristina; Núñez Medrano, Juan Ángel; López San Juan, Fernando José; Sánchez Pereda, Daniela; Capiz Correa, Daniel Raúl; Velasco, Leopoldo (Journal of cosmetic dermatology, 2020)
Objective To propose an algorithm of treatment for sudden visual loss following filler injections and perform an English‐written literature search for assignment of evidence level and grade recommendation. Methods Algorithm of treatment includes ocular physical Maneuvers, hyAluronidase administration, intravenous STEroids, intraocular pressure Reduction, and Supplemental Oxygen (M.A.STE .R.S) based on previous acute management reports. Special consideration for algorithm buildup was made for ophthalmic diseases that share physiopathological features such as central retinal artery occlusion, systemic vasculitis affecting vision, and acute glaucoma. Finally, a systematic cross‐review of the reported cases with visual loss was done to identify the level of evidence and grant a recommendation grade. Results A search through PubMed and Medscape databases for English‐written scientific papers using the terms facial filler, retinal artery occlusion, management, treatment, complications, and adverse events quoted a total of 46 papers (190 cases) which were then analyzed. A high variability on management for treatment of sudden visual loss after facial filler injections was observed. This was attributed partially to the great diversity of medical specialists performing cosmetic facial procedures such as dermatologists, plastic surgeons, esthetic doctors and ophthalmologists, and the lack of high evidence level studies. Conclusions The proposed algorithm provides an initial guideline based on prior literature reports and physiopathology involving facial filler injection complications. Analysis identified 22 successfully treated cases with vision recovery (11.57%). Ocular physical maneuvers had the best evidence‐based level and grade recommendation (A) for the management of acute vision loss secondary to facial filler injections.